Fabrication of 3D thin polymer structures for hybrid sensors and actuators - Park, J; Kim, J; Roh, D; Park, S; Kim, B; Chun, K (MEMS 2006: 19TH IEEE INTERNATIONAL CONFERENCE ON MICRO ELECTRO MECHANICAL SYSTEMS, TECHNICAL DIGEST, 2006)
This paper presents a novel technique to fabricate complex 3 dimensional thin polymer structures with different geometries on both sides for hybrid sensors and actuators. To realize complex 3D polymer structures, we fabricate a 3D-micromolding aligner which can make two molding masters be aligned within 2 mu m and allows applying high pressure to construct thin membrane under 10 mu m. Using this system, we make thin polymer structure with complex 3D geometries successfully. Generally, complex 3D microstructures are used in microfludics system, such as micromixers, valves and pumps. In this study, we shows a new opportunity of complex 3D structures, that is, as versatile hybrid sensors for understanding structural and functional changes of cells and as micro scale hybrid actuators that can be operated independently without any external power sources.